Deep Investigation Into the Electrodeposition Model of Mg Battery Anode - Zhou, Yingmei; Wei, Zhengnan; Xu, Jing; Chen, Changguo (Frontiers in Chemistry, 2022)
The electrocrystallization mechanism of Mg electrode in aqueous electrolyte was comprehensively investigated. The dimensionless processed transient curves confirmed that the initial nucleation/growth process of Mg electrode in aqueous solution followed the diffusion-controlled three-dimensional instantaneous nucleation model.